SERS Characterization of the Indocyanine-Type Dye IR-820 on Gold and Silver Nanoparticles in the Near Infrared - Tatiana B. V. Neves; Gustavo F. S. Andrade (Journal of Spectroscopy)
The Raman spectrum of the indocyanine-type dye IR-820 has been assigned for both solid and solution. SERS spectra of IR-820 on both silver and gold nanoparticles suspensions excited at 1064 nm were obtained. AgNPs allowed the detection of the dye through SERS down to 0.1 micromoles per liter; for the AuNPs the lowest concentration of the dye detectable was 10 micromoles per liter. Changes in the SERS relative intensities compared to the Raman spectrum in solution are subtle, mostly due to the preresonance effect of the dye. However, a perpendicular orientation relative to the metallic surface was inferred for the dye on both AgNPs and AuNPs. The easily distinguishable SERS spectra of the dye excited at 1064 nm, together with the high biological compatibility of cyanine dyes, are both indicative that IR-820 could be used as a high-performance probe molecule for SERS.